Hovenia dulcis: a Chinese medicine that plays an essential role in alcohol-associated liver disease - He, Yi-Xiang; Liu, Meng-Nan; Wang, Yang-Yang; Wu, Hao; Wei, Mei; Xue, Jin-Yi; Zou, Yuan; Zhou, Xin; Chen, Hui; Li, Zhi (Frontiers in Pharmacology, 2024)
Globally, alcohol-associated liver disease (ALD) has become an increased burden for society. Disulfirams, BZDs, and corticosteroids are commonly used to treat ALD. However, the occurrence of side effects such as hepatotoxicity and dependence, impedes the achievement of desirable and optimal therapeutic efficacy. Therefore, there is an urgent need for more effective and safer treatments. Hovenia dulcis is an herbal medicine promoting alcohol removal clearance, lipid-lowering, anti-inflammatory, and hepatoprotective properties. Hovenia dulcis has a variety of chemical components such as dihydromyricetin, quercetin and beta-sitosterol, which can affect ALD through multiple pathways, including ethanol metabolism, immune response, hepatic fibrosis, oxidative stress, autophagy, lipid metabolism, and intestinal barrier, suggesting its promising role in the treatment of ALD. Thus, this work aims to comprehensively review the chemical composition of Hovenia dulcis and the molecular mechanisms involved in the process of ALD treatment.